Combined bone scintigraphy with 99mTc-MDP and 99mTc-ciprofloxacin in differentiation of hip and knee prosthesis aseptic loosening and infection: A preliminary study - Pucar Dragan; Janković Zoran; Baščarević Zoran; Starčević Srđan; Čizmić Milica; Radulović Marija; Šišić Marija; Dugonjić Sanja; Jauković Ljiljana; Ajdinović Boris (Vojnosanitetski Pregled)
Background/Aim. Although the number of new primary implantation of hip and knee prostheses every year increases, the rate of failed arthroplasty is nearly the same. The main question is whether it is an aseptic instability or instability caused by infection. The aim of this preliminary study was an attempt with combined 99mTc-ciprofloxacin and 99mTc-methylene diphosphonate (MDP) bone scintigraphy to improve diagnostic accuracy in the differentiation of hip and knee prosthesis aseptic loosening and periprosthetic joint infection. Methods. Inclusion criteria of patients for this study were based on suspected periprosthetic joint infection: painful prosthetic joint, restricted joint movements and increased value of erythrocyte sedimentation rate or levels of C-reactive protein. We examined 20 patients with implanted 14 hip and 6 knee prosthesis. All patients also underwent plain radiography of suspected joint. In all patients, three-phase 99mTc-MDP bone scintigraphy was performed. Three to five days after the bone scan, we performed scintigraphy using 99mTc-ciprofloxacin with the calculation of accumulation index. Periprosthetic joint infection was confirmed on the basis of microbiological findings. Results. Periprosthetic joint infection was confirmed in fourteen of twenty observed joints, in five of them the aseptic loosening was present and in one patient’s symptoms were not related to the prosthesis (poor biomechanics of prosthetic joints caused by weaknesses of muscle). Estimated sensitivity/specificity for 99mTc-MDP bone scintigraphy alone were 100/17%; for 99mTc-ciprofloxacin scintigraphy were 85,7/100%. Sensitivity and specificity were 92,3% and 83,3%, respectively for results obtained with combined assessment by both methods. Our study confirmed the high negative predictive value of 99mTc-MDP bone scan. The negative result of bone scan virtually excludes the possibility of periprosthetic infection. On the other hand, positive findings of 99mTc-MDP scintigraphy cannot with certainty confirm the infection. Conclusion. Combined 99mTc-MDP scintigraphy with 99mTc-ciprofloxacin scintigraphy significantly increases the ability of differentiation of aseptic loosening from periprosthetic joint infection.